Análise de uma sequência de ensino investigativo sobre decompositores na promoção da alfabetização científica de um grupo de alunos do 6º ano do ensino fundamental - Caprini, Jessica Cremonini (2019)
The following research aimed to analyze an Investigative Teaching Sequence on decomposers in the promotion of Scientific Literacy, from a group of 6th grade elementary school students from a public school in the city of Iconha - ES. Based on the Teaching of Research Science as a didactic approach and on Scientific Literacy,It was used a qualitative approach to intervention research. The production of data occurred from the elaboration and application of an Investigative Teaching Sequence. The analysis were based on the Scientific Literacy axes considering the students speeches during the interactions and the logbook records. The application of SEI enabled the identification of evidence of Scientific Literacy such as: serialization, organization and classification of information, logical and proportional reasoning, hypothesis raising, justification and explanation. In the educational product we introduce SEI to Science teachers in order to reflect on teaching practice and propose ways for other teachers to use Science teaching by research in the development of didactic sequences in order to achieve Scientific Literacy.